THE THEORY OF SOCIAL MOBILITY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Social mobility theory investigates how individuals and groups move within a society’s stratification system and what conditions foster or hinder that movement. Classical models emphasized intergenerational comparisons of occupational or income status, treating mobility largely as upward “climbing.” Contemporary scholarship reframes mobility as a multidimensional, life-course process shaped by economic, human, social, digital, and spatial capitals. This article traces the intellectual evolution of social mobility theory, outlines its central concepts and mechanisms, reviews major empirical findings, and assesses the policy levers that can widen equitable mobility in the twenty-first century.